The History of the University at the Science Festival in Spain - Hernández Díaz, José María (CIAN-Revista de Historia de las Universidades, 2020)
Every academic year, at the beginning of the course, all the universities in Spain hold a series of events that are part of what we can call the Science Festival, using a 19th century positivist language. Within this celebration, the inaugural lesson, which is delivered by a teacher chosen for this purpose, and who is usually an academic of prestige in his academic specialty, acquires special significance. In a patient manner we have first formed a database of 2165 units, speeches or opening lessons delivered at the 87 Spanish universities, public and private, from 1939 to 2019. Later we have been able to form several categories of analysis, which host different thematic fields of university life. One of these categories is the “History of Universities”, which allows us to obtain a quota of 54 units or inaugural lessons dealing with this topic. From his reading and study we obtain very significant conclusions for the particular history of some universities, especially those considered as classics, but also for the whole of the Spanish university, from its origins in the Middle Ages to the 21st century. It is shown as well as the history of the universities, through a documentary source such as the opening lessons, can be consolidated as a field within the studies on higher education, and also on the institutional history.